A score function as quality measure for cardiac image enhancement techniques assessment (2019)
A score function useful as a quantitative measure of the performance of the medical image enhancement techniques is reported in this paper. The measure proposed is based on merging of full–reference and blind–reference image enhancement measures. The score function is the average of the weighted sum of the image enhancement measures normalized between zero and one. The novel measure is validated considering as a hypothesis that values maximizing score function have that maximize the values of the metrics (Dice coefficient) used to evaluate certain previously reported cardiac image segmentation approach. The values of score function and Dice score reached the maximum value for the same cardiac volumes segmented.